Analysis and practical validation on a multi-linkage scissor platform's drive system for the satellite test facilities - Norsahperi, N.M.H.; Ahmad, Salmiah; Toha, Siti Fauziah; Mahmood, I.A. (Inderscience Publishers, 2021)
This paper evaluates a modified structural analysis in measuring the reaction forces on the multi-linkage scissor mechanism driven by a ball-screw system. The proposed structural-virtual work (SV) analysis takes into account all reaction forces on the designed linkages to evaluate the accurate actuator’s sizing and as the consequence, the overall machinery development cost will be significantly reduced. The idea is proven in three ways: analytical analysis, simulation analysis and experimental analysis based on the developed prototype. The simulation study has shown that the estimated torque is successfully reduced by 29% as compared to the conventional approach. The superiority of the proposed analysis is confirmed by 12% error between the simulation and results from the developed prototype. The successful method proposed in this paper can be further used for all multi-linkage systems in the heavy-vehicle industry that requires accurate actuators’ sizing.